VLSI Implementation Of 2-D Discrete Cosine Transform Algorithm For Image Compression - Islam, Md. Shabiul (2008)
In this dissertation, we focus on the use of 2-D Discrete Cosine Transform (DCT) technique since it has a modular architecture, and is therefore,suitable for Very Large Scale Integration implementation. The 2-D DCT is also at the heart of the JPEG standard for still-image compression.